A Review on Biodegradable Plastics and Its Future (International Journal of Innovative Research in Engineering & Management, 2023)
Synthetic polymers play a significant role  in a variety of industries, especially packaging. However, it  has a negative impact on the environment and creates issues  with trash disposal and consumption. As a result, there's a  trend toward replacing the polymer with a biodegradable  polymer that goes through a procedure. This study includes  information on consumption, biodegradation,  commercialization dependability, and renewable energy  generation. Microorganisms may break down biodegradable  and compostable materials into water, carbon dioxide,  mineral salts, and new biomass in a certain amount of time.  The circumstances under which a biodegradable or  compostable plastic item dissolves and how fast it degrades  are very dependent on the environment under which it is  discarded. Commercialized biodegradable polymers  includes starch based plastic, bacteria’s based plastic,  cellulose-based plastics, soy-based plastics, lignin-based  plastics, & naturally made fibers reinforced plastic. The  manufacture of the kind of the materials & it introductions to markets are crucial for environment.
Keywords: Biodegradable Polymer; Starch Based Plastic; Bacteria Based Plastic; Soy Based Plastic; Cellulose Based Plastic; Lignin Based Plastic; atural Fiber Reinforced Plastic